Analysis of the academic and professional profile of the members of research ethics committees implants in institutions of the federal network of professional, scientific and technological education of the northeast region of Brazil (Research, Society and Development, 2019)
This article aims to identify the profile of members of Research Ethics Committees Involving Human Beings (CEPs) located in institutions of the Federal Network of Professional, Scientific and Technological Education located in the Northeast region through research on institutional documents and analysis of data available on the Lattes online academic curriculum platform. In methodological terms, this research is a study with a quantitative approach of documentary research type. The data concerning the academic formation and the professional performance of the members of CEPs analyzed were collected exclusively from the online platform of academic curricula Lattes. The results showed that the members of the CEPs located in the Federal Institutes of Education of the Northeast region are predominantly public servants, teachers of Basic Education, Technical and Technological and Administrative Technicians in Education, who joined the Federal Network of Professional, Scientific and Technological Education as of 2008.